Tinjauan Atas Penetapan Harga Pokok Penjualan Pada PT Kimia Farma Apotek Cabang Alauddin - Masnawaty Sangkala (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2022)
This study aims to determine the calculation in determining the cost of goods sold at PT Kimia Farma Apotek Alauddin branch. The variable that is the focus of this research is therecap of Cost of Goods Sold Calculation Data at PT Kimia Farma Apotek Alauddin branch and then measured by comparing it with the determination of the cost of goods sold at the company with calculations according to theory. The population in this study is the data on the calculation of Cost of Goods Sold at PT Kimia Farma Apotek Alauddin branch. Meanwhile, the sample in this study is data on sales of the Company's merchandise in March 2020. Data analysis was carried out using descriptive analysis. The results of this study show that the calculation in determining the cost of goods sold at PT Kimia Farma Apotek Alauddin branch does not deviate from the theory proposed by Sujarweni.